2023
DOI: 10.1186/s12886-023-02897-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of bilateral implantation of new generation monofocal IOL enhanced for intermediate distance and conventional monofocal IOL in a Korean population

Abstract: Background To compare the clinical outcomes of bilateral implantation of enhanced intermediate function intraocular lenses (IOLs) and standard monofocal IOLs. Methods In this prospective, randomized, comparative controlled study, we compared the visual outcomes of patients who underwent bilateral cataract surgery at the Kangbuk Samsung Hospital, Sungkyunkwan University School of Medicine, with either enhanced monofocal IOLs (Tecnis Eyhance, ICB00, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
2
7
2
Order By: Relevance
“…one Snellen line) and a mean difference in binocular UIVA of −0.17 logMAR (almost two Snellen lines). The larger difference in binocular UIVA could be attributed to a more myopic residual manifest spherical equivalent reported in most of the available comparative studies, 7 , 9 , 10 , 14 , 18 , 21 which was, on average, higher than the residual myopia in the non-dominant eye in the current study. On the other hand, a meta-analysis of Redruello-Guerrero et al 37 focused on distance-corrected intermediate vision (DCIVA) comparison and found −0.21 logMAR difference between ZCB00 and ICB00 models in binocular DCIVA 2 weeks to 1 month postoperatively, and −0.11 logMAR difference six months postoperatively.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…one Snellen line) and a mean difference in binocular UIVA of −0.17 logMAR (almost two Snellen lines). The larger difference in binocular UIVA could be attributed to a more myopic residual manifest spherical equivalent reported in most of the available comparative studies, 7 , 9 , 10 , 14 , 18 , 21 which was, on average, higher than the residual myopia in the non-dominant eye in the current study. On the other hand, a meta-analysis of Redruello-Guerrero et al 37 focused on distance-corrected intermediate vision (DCIVA) comparison and found −0.21 logMAR difference between ZCB00 and ICB00 models in binocular DCIVA 2 weeks to 1 month postoperatively, and −0.11 logMAR difference six months postoperatively.…”
Section: Discussioncontrasting
confidence: 51%
“…Although there might be some variation in the level of improved intermediate or near vision comparing Tecnis ICB00 and ZCB00 model between available studies, whenever intermediate vision was evaluated with patient-reported outcomes (satisfaction or spectacle independence), Tecnis Eyhance was always superior. 7 , 8 , 10–12 , 14 , 18 , 20 , 28 Most importantly, the published studies strongly agree that there is no difference between the two lenses in the perception of visual phenomena or satisfaction with distance vision. 7–12 , 17 , 20 , 21 Our study corroborated these findings in a larger population patients, finding no difference in overall satisfaction with vision or difficulties with optical side effects.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Many studies have found that intermediate visual acuity is enhanced when ICB00 is inserted compared to a general monofocal IOL [ 6 9 ]. Meanwhile, photic phenomena such as glare or halo and contrast sensitivity were found to be comparable to monofocal and more improved than the extended depth of focus (EDOF) [ 10 12 ]. However, to our knowledge, no studies exist on the preoperative ocular parameters that affect the quality of near, intermediate, and distance visual acuities of the ICB00 or DIU.…”
Section: Introductionmentioning
confidence: 99%